Pengaruh Dimensi dalam Fraud Diamond dan Penyalahgunaan Teknologi Informasi Terhadap Perilaku Kecurangan Akademik (Universitas Negeri Semarang, 2022)
This study aims to analyze the influence of the dimensions in the fraud diamond consisting of pressure, opportunity, rationalization, and ability, as well as the misuse of information technology on academic fraud behavior in accounting economic education students at the State University of Semarang. The population in this study were 160 students of accounting economics education class 2015 Semarang State University. The sample was calculated using the Slovin formula, obtained 114 students. The sampling technique used is proportional random sampling. The collection method used a questionnaire and the data were analyzed by multiple linear regression. The results showed that simultaneously pressure, opportunity, rationalization, ability, and misuse of information technology had a positive and significant effect on academic cheating behavior. Partially, pressure, opportunity, rationalization and misuse of information technology have a positive and significant effect on academic cheating. The ability to cheat has no effect on academic cheating behavior